Paradigma Pengembangan Masyarakat Islam - Sumpena, Deden (Jurnal Ilmu Dakwah, 2008)
Based to tauhidullah principle in developing Islamic society is absolute. The society self has to own conscious to that principle. The principle improve to all act in mendirikian tatana ilahi. Its implementation can be analized in forms:Â  menjadilan Al-Qurâan as life reference, menjadikan Islam become ideology and way of life, having conscious abut human position as holder amanat (khilafah), developing brotherhood based faith, and menghormati differenciate 0f isme and believe.